Suzuki–Miyaura Cross-Coupling Reactions of Unactivated Alkyl Halides Catalyzed by a Nickel Pincer Complex - Di Franco, Thomas; Boutin, Nicolas; Hu, Xile (Synthesis, 2013)
A nickel(II) pincer complex, [(MeN2N)Ni-Cl], was used to catalyze alkyl–alkyl and alkyl–aryl Suzuki–Miyaura coupling reactions of unactivated alkyl halides. The coupling of 9-alkyl-9-borabicyclo[3.3.1]nonane and 9-phenyl-9-borabicyclo[3.3.1]nonane reagents with alkyl halides was achieved in modest to good yields. The reactions tolerated a variety of useful functional groups including ester, ether, furan, thioether, acetal, and Boc groups.
Keywords: cross coupling; nickel; alkyl halides; pincer complex; Suzuki–Miyaura coupling